2004
DOI: 10.1227/01.neu.0000143033.36582.40
|View full text |Cite
|
Sign up to set email alerts
|

New Variants of Malignant Glioneuronal Tumors: A Clinicopathological Study of 40 Cases

Abstract: NFP immunostaining is required to identify MGNTs accurately. Their distinction from malignant gliomas is of paramount clinical importance, particularly for neurosurgeons, because gross total surgical resection may be curative in some cases. Finally, MGNTs may account for the long-term survival and/or occurrence of metastases demonstrated in a subset of malignant gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 44 publications
5
83
2
2
Order By: Relevance
“…In a study performed by Valret et al on malignant glioneuronal tumors (MGNTs), all tumors coexpressed GFAP and NFP, in which NFP immunostaining was performed without antigen retrieval. The staining result was poor (10/12) in comparison with tumors stained with antigen retrieval (Varlet et al, 2004). In our study, to decrease false negative results, once the sections were stained without antigen retrieval and again were stained with antigen retrieval.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In a study performed by Valret et al on malignant glioneuronal tumors (MGNTs), all tumors coexpressed GFAP and NFP, in which NFP immunostaining was performed without antigen retrieval. The staining result was poor (10/12) in comparison with tumors stained with antigen retrieval (Varlet et al, 2004). In our study, to decrease false negative results, once the sections were stained without antigen retrieval and again were stained with antigen retrieval.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies found that the antigen retrieval process may induce nonspecific immunostanining (Varlet et al, 2004). In a study performed by Valret et al on malignant glioneuronal tumors (MGNTs), all tumors coexpressed GFAP and NFP, in which NFP immunostaining was performed without antigen retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 40 cases of grade III or IV glioma demonstrated coexpression of GFAP and NFP as essential to the diagnosis of GBM-PNET [165]. Furthermore, a lack of recurrence was observed in 36% of cases, which underwent gross total resection resulting in a mean survival of 44 months.…”
Section: Glioblastoma Multiforme With Primitive Neuroectodermal Featuresmentioning
confidence: 99%
“…[Table6] As the clinical and histopathological properties of those tumors have been described only recently, the number of cases reported in the literature is limited. The largest series published on these tumors belong to Varlet et al [ 21] (n=40) and Perry et al (22) (n=53). These studies highlighted the clinical, radiological, and histopathological differences of GB-PNET from classic GBM.…”
Section: Discussionmentioning
confidence: 99%